Kritik Sastra Arab pada Masa Yunani - Ismail, Ismail; Tasnimah, Tatik Maryatut; Ritonga, Ridwan (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
The purpose of this study is to examine the development of literary criticism in the Greek period. The data collection method used in this study is the literature review method. The researcher will search all data related to this study and record the data. The approach used in this study is a historical approach where researchers look for stories related to the history of the development of Arabic literary criticism in the Greek period. From the results of this research can be found out about the understanding and classification of Arabic literary criticism. In addition, this study provides information on Arabic literary criticism in Greek times, Greek influence on Arab criticism through reading, and criticism of orientalist books in the context of Greek influence. In literary criticism, the task of teaching literature with the support of literary theory is literary criticism, especially oral literary criticism, using works of literary criticism to explain abstract literary theories.Keywords - Criticism, Arabic Literature, Greek.